3D Porous Metallic Boron Carbide Crystal Structure with Excellent Ductility. Issue 12 (17th October 2021) - Hussain, Kashif; Muhammad, Imran; Wu, Wei; Qie, Yu; Mahmood, Tariq; Sun, Qiang
Abstract: It is well established that metal atoms can be used to regulate porosity in synthesis and porous structures can be obtained by removing metal atoms. Motivated by a recent synthesis of 2Sr@B6 C6, it is found that when Sr atoms are removed, the resulting 3D porous BC structure (3D‐B6 C6 ) with reduced symmetry is stable thermally, dynamically, and mechanically. More importantly, different from the widely studied semiconducting B‐rich boron carbides, the 3D‐B6 C6 is metallic ; And different from C‐rich boron carbides with high hardness and brittleness, the 3D‐B6 C6 is found to be a novel 3D boron carbide crystal showing excellent ductility with Pugh's ratio of 2.24, low Vickers hardness of 8.66 GPa, and universal anisotropy index of 2.62. This study expands the boron carbides family with new features. Abstract : A porous 3D‐B6 C6 crystal, derived from the recently synthesized 2Sr@B6 C6, is theoretically predicted to be metallic, ductile, and soft with low Vickers hardness.